Karakteristik Sensoris Selai Karendang (Carissa carandas) Dengan Penambahan Konsentrasi Gula - Pattiruhu, Gysberth; Mustamu, Sofia (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
Karendang is one of the thorny shrubs that has a dark red color and has a slightly sour taste. Karendang has a high moisture content, so it will quickly decay, so further processing into jam is needed. Jam is one of the semi-wet foods made from a mixture of sugar. The purpose of this study was to determine the concentration of sugar in making karendang jam against the sensory characteristics of karendang jam. The design used is a Complete Random Design (RAL) with a treatment of adding sugar concentration consisting of 4 levels, namely the addition of sugar 25%, 50%, 75% and 100% and repeated 3 times. Hedonic observations made consisting of color, taste, aroma, texture and smearing power were carried out by 30 rather trained panelists. The results showed that the G2 treatment (50% added sugar) had the color, taste, aroma, texture and spreadability preferred by the panelists and was the best treatment for making karendang jam.